Smart-speaker technology and intellectual disabilities: agency and wellbeing. - Smith, Elizabeth; Sumner, Petroc; Hedge, Craig; Powell, Georgina (Disability & Rehabilitation: Assistive Technology, 2023)
Mainstream intelligent personal assistants (IPAs, e.g., Amazon Echo and Google Home) offer an unprecedented opportunity to enhance agency and wellbeing among vulnerable groups across health and social care. However, unintended consequences and barriers to use are possible. We conducted a mixed-methods semi-randomized controlled trial among individuals with intellectual disability (ID), providing IPAs to an intervention group (N = 22), but not a control group (N = 22). Semi-structured interviews on device use and daily life were conducted with individuals with ID. Observation surveys were also collected from support staff. Key themes were identified using thematic analysis. We also collected quantitative agency and wellbeing data. A separate group of 40 individuals who had already received IPAs were additionally assessed, as well as their support staff. Four themes were identified: (1) social value, (2) entertainment, (3) perceived agency, (4) challenges, perseverance, training/support needs. Opinions regarding IPAs were overwhelmingly positive. Most individuals qualitatively reported improved sense of agency and IPAs enabled many individuals to access features associated with wellbeing, but there was no significant change in the quantitative measure. Some individuals experienced challenges related to pronouncing and remembering IPA phrases; however, perseverance was common. This study increases our understanding of the ways smart speakers can be used to enhance life quality among individuals with ID, and the nature of barriers faced. In conclusion, IPAs are cost-effective complementary support for vulnerable populations, but additional training is required to realize all potential benefits. Individuals with intellectual disability (ID) in supported living are able to use mainstream smart-speakers to access features associated with supporting wellbeing and social communication. They also reported that smart speakers made them feel better able to do things for themselves. A number of individuals with ID and their support staff identified a need for training and support to get the most out of smart speakers in future.